The use of echocardiography as a routine perioperative monitoring standard: The perspective of a cardiothoracic anesthesiologist - Nada, I Ketut Wibawa; Pradhana, Adinda Putra (Bali Journal of Anesthesiology, 2019)
INTRODUCTIONIn the era of medicine that has been very advanced as it is today, we as anesthesiologists are required to be able to provide anesthetic services that are comfortable but still safe. Throughout the world, there are more than 300 million major surgery each year, and major cardiovascular adverse events are a significant cause of perioperative morbidity and mortality.1 This certainly relates to the nature of anesthetic agents that are mostly cardiovascular-depressant. Anesthetic agents such as propofol, ketamine, opioids, inhalation anesthetic agents, and many others, can directly affect the cardiovascular system.2While the major cardiac event occurred during perioperative events is also quite high. Especially for the patients in the perioperative period who will undergo non-cardiac surgery. This frequently reduces the alertness of an anesthesiologist, especially when performing perioperative monitoring. A study from Smilowitz et al.,1 showed that out of 10,581,621 patients admitted to hospital for major non-cardiac surgery plans, 317,479 (3%) patients had experienced major cardiac events. Which can be illustrated that major cardiac events occur in 1 in 33 patients treated for major non-cardiac surgery. Echocardiography is a safe, relatively inexpensive and well-tolerated action for patients.3Regular use of echocardiography in the perioperative period can certainly help to predict and even reduce major events adverse cardiac events. It is good to be used as a guide for making decisions in carrying out actions, as well as for monitoring the patient's condition regularly during the perioperative period. The use of echocardiography so far has been used for both diagnosis and management in the field of cardiology and is used by another specialist as well, although anesthesiologists do not use it in the perioperative period as a routine manner. Meanwhile, the role of an anesthesiologist as a perioperative doctor has become something that other specialties have begun to rely on.4